Responding to Islamic religious conducts: Situating morality through critical reading literacy task on cartoons for Indonesian EFL muslim learners - Kusumaningputri, Reni (Universitas Pendidikan Indonesia, 2019)
Due to terrorism and muslim discourse, Islamic outfits receive negative images by other muslims. Therefore, there is a need to engage muslim university students with critical reading literacy to situate morality. Through the task, the students play two important roles: text participants and text analysts. In this study, cartoons were used as materials for exercising critical reading and eliciting students’ responses to beliefs, values, identities, and ideologies inherent in the cartoons. Anchoring in Critical Discourse Analysis through semantic and critical practices, the participants involved in stages of exercising critical literacy on cartoons as an attempt to situate Islamic morality. The tasks enable learners to sharpen their understanding of how the society works as different systems and to invigorate their self-view on the awareness that human constantly changes identity. The results of the study reveal that the task enables learners to reflect, react, and posit themselves as muslims and global citizens.